(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2026)
Adolescence is a critical period of growth and development that is highly vulnerable to nutritional problems, including anemia, stunting, obesity, and micronutrient deficiencies. These conditions are often associated with unhealthy dietary habits, such as skipping meals, irregular eating patterns, and inadequate intake of nutritious foods. Regular consumption of breakfast, lunch, and healthy snacks is essential to support adequate nutrient intake and maintain optimal nutritional status. This study aimed to determine the relationship between breakfast, lunch, and healthy snack consumption and the nutritional status of adolescent girls at SMP Negeri 2 Pekanbaru. A quantitative study with a descriptive cross-sectional design was conducted among 71 seventh-grade female students selected using total sampling. Dietary habits were assessed using a structured questionnaire, while nutritional status was determined by Body Mass Index (BMI). Data were analyzed using descriptive statistics and the Chi-Square test. The findings showed significant relationships between breakfast consumption and nutritional status (p = 0.004), lunch consumption and nutritional status (p = 0.004), and healthy snack consumption and nutritional status (p = 0.004). Adolescent girls with healthier eating habits were more likely to have normal nutritional status than those with poor dietary habits. In conclusion, breakfast, lunch, and healthy snack consumption are significantly associated with the nutritional status of adolescent girls. Promoting healthy dietary habits through nutrition education is essential to support optimal growth and development during adolescence. These findings provide useful evidence for schools, parents, healthcare professionals, and policymakers in designing effective nutrition education programs to encourage healthy eating behaviors among adolescents.